Adaptive and Natural Computing Algorithms
DOI: 10.1007/3-211-27389-1_111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Genetic Algorithms for Locking-Cache Contents Selection in Real-Time Systems

Abstract: Locking caches, providing full determinism and good performance, are a very interesting solution to replacing conventional caches in real-time systems. In such systems, temporal correctness must be guaranteed. The use of predictable components, like locking caches, helps the system designer to determine if all the tasks will meet its deadlines. However, when locking caches are used in a static manner, the system performance depends on the instructions loaded and locked in cache. The selection of these instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In [17], a methodology to select a set of instructions to be preloaded in the cache using a genetic algorithm is proposed. In [18], various algorithms to select a set of instructions to be locked in cache are compared. These algorithms show better performance and simultaneously estimate a tight upper bound of the response time of tasks.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [17], a methodology to select a set of instructions to be preloaded in the cache using a genetic algorithm is proposed. In [18], various algorithms to select a set of instructions to be locked in cache are compared. These algorithms show better performance and simultaneously estimate a tight upper bound of the response time of tasks.…”
Section: Related Workmentioning
confidence: 99%
“…These algorithms show better performance and simultaneously estimate a tight upper bound of the response time of tasks. Techniques discussed in [14][15][16][17][18] are used mainly to evaluate predictability in a single-core system. These techniques are not capable of power estimation -a crucial design factor for embedded systems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the sequential version of the genetic algorithm presented in [15]. Eight different versions have been evaluated.…”
Section: Gamentioning
confidence: 99%
“…Although it is possible to use other metrics such as task slack or response times, in [16] it is shown that using the system utilisation in the fitness function offers similar results than using these aforementioned metrics.…”
Section: Fitness Functionmentioning
confidence: 99%